Relevansi dan Respons Pendidikan Muhammadiyah terhadap Tantangan Era Disrupsi Digital: Sebuah Kajian Sistematis: Sebuah Kajian Sistematis - Setiawati, Ina; Abdul Hakim, Sudarnoto; Sari, Zamah; Dwi Fajri, Muhamad (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2025)
The era of disruption presents significant challenges for the world of education, particularly in curriculum relevance, learning innovation, and technology integration. As Indonesia’s largest Islamic educational institution, Muhammadiyah possesses distinctive characteristics that respond to these dynamics. This study aims to identify and synthesise findings from scholarly literature regarding the relevance of Muhammadiyah education in addressing educational challenges in the disruption era through a Systematic Literature Review (SLR) approach. Regarding the PRISMA guidelines, 38 articles meeting the inclusion criteria were thematically analysed. The results indicate that Muhammadiyah education has developed innovative strategies in strengthening Islamic values-based and technology-integrated curricula, transformational leadership, and social empowerment. However, several implementation challenges remain, such as digital gaps and the need for teachers’ technology literacy training. This SLR concludes that Muhammadiyah education holds strong adaptive potential but requires systemic and collaborative reinforcement to address future challenges sustainably.